The golden cup - Plain, Belva (Dell Publishing, 1987)
A woman of hidden desires, Hennie De Rivera has none of the wealth enjoyed by her relatives, the Werner banking dynasty. But tall, shy Hennie has grand dreams, especially of daring activist Dan Roth, who invites controversy by fighting for New York's poorest immigrants. Breaking society's rules may have devastating consequences for this passionate woman -- and for her nephew Paul Werner, who weds his debutante fiancee while still yearning for his mother's beautiful maid, Anna Friedman. And amid heartbreaking discoveries and the gathering clouds of World War I, the stirring family saga begun in Evergreen continues with an unforgettable tale of forbidden passions, intimate secrets, and sweeping social change.